Towards a Novel Memory Biomarker for Alzheimer's Disease Relying on Eeg-Based Mobile Brain Imaging Technologies (2016)
Background: Reliable and affordable biomarkers for Alzheimer’s disease (AD) are currently lacking. Those available are (1) invasive, (2) weakly associated to cognitive and functional decline, (3) non-specific, (4) expensive, and (5) attached to hospital facilities. A recently developed Visual Short-Term Memory Binding (VSTMB) test has addressed the first three needs. Recent studies indicate that combined with EEG techniques, it can yield a mobile brain imaging tool which would hold biomarker properties. Here we present recent studies that have tested this hypothesis aiming also at providing solutions to needs 4 and 5. Methods: Patients in the Mild Cognitive Impairment (MCI) stages of familial (E280A-PSEN1 mutation) and sporadic AD were assessed with the VSTMB test and comprehensive neuropsychological protocols. In the VSTMB test patients studied and temporarily held visual arrays of shapes only or shapes combined with colours (i.e., binding). They then detected changes between the studied and a test arrays. For arrays of shapes new shapes were introduced during the test (50% of trials), whereas for shape-colour bindings, shapes swapped their colours. We recorded the EEG during the task and 10 minutes resting period using high density electrode arrays. We additionally recorded a subsample of healthy young individuals using a low density array linked to novel mobile technology. The data was analysed using ERP and Brain Connectivity methods. Results: Behavioural and electrophysiological data showed the previously reported dissociation whereby VTSM for bindings, but not for shapes, was more severely affected in patients than in controls. Disruption of a brain network which involves frontal and parietal-occipital regions accounted for such impairments. Combining behavioural and electrophysiological measures of STMB performance we correctly classified 100% of the familial cases, and such a phenotype was present in sporadic MCI cases whose subtype is known to hold the highest risk for dementia. Brain responses from the most discriminative hubs of the network were very similar whether recorded with high or low density electrode arrays. Conclusions: The assessment of VSTMB integrated with EEG-based methods yields a novel memory biomarker for AD. When relying on mobile brain imaging tools, such biomarker could potentially meet all the above mentioned needs.